Graphene: Two‐Stage Metal‐Catalyst‐Free Growth of High‐Quality Polycrystalline Graphene Films on Silicon Nitride Substrates (Adv. Mater. 7/2013). (14th February 2013) - Chen, Jianyi; Guo, Yunlong; Wen, Yugeng; Huang, Liping; Xue, Yunzhou; Geng, Dechao; Wu, Bin; Luo, Birong; Yu, Gui; Liu, Yunqi
<x xml:space="preserve">Abstract</x> High‐quality graphene polycrystalline films are directly synthesized on dielectric silicon nitride substrates by using two‐stage metal‐catalyst‐free chemical vapor deposition. Thus large‐scale electronic devices are easily fabricated on these films without complicated transfer processes and their associated problems. The method is compatible with current Si processing techniques. Further details can be found in the article by Yunqi Liu and co‐workers on page 992. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>